PENGARUH KECANDUAN PONSEL TERHADAP PEMBENTUKAN KARAKTER ANAK USIA EMPAT SAMPAI SEPULUH TAHUN DI GEREJA BETHEL INDONESIA TABGHA BATAM CENTER - Intan Suriyanti; Sri Rahayu (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
In simple terms, smartphone addiction can be interpreted as a condition where a child is addicted or dependent on the excessive use of smartphones. Excessive use of smartphones without proper supervision from parents can have an impact that is not good for children because they will become children who are not optimal, can suffer from health problems, can have decreased brain abilities and other consequences. The research method used in this study is a quantitative method based on quantification in data collection and analysis to test the hypothesis that the researcher has set. The research was conducted at the Indonesian Bethel Church Tabgha Batam Center, which is located in the service area of the Riau Islands Regional Worker's Body, the Indonesian Bethel Church and is domiciled in Batam City, from October 2021 to February 2022. The results of the study prove that (1) Smartphone addiction in children aged four to ten years is in the range of 78.33 - 87.99: moderate to high rate, and (2) Character formation of children aged four to ten years is in the range of 155.61 – 168.87: high rate. This study also found (3) That the contribution of smartphone addiction in children aged four to ten to form the children's character is 36%. The magnitude of the direct influence of mobile phone addiction on the character formation of children aged four to ten years is a constant of 93,734; This means that if the congregation's cell phone addiction's value (X) is 0, the negative influence on the formation of the child's character (Y) at the Bethel Church of Indonesia Tabgha Batam Center has a value of 93,734. The value of regression coefficient of the mobile phone addiction variable (X) is 0.824; it means that if the addiction to smartphones is increased once, it will increase the value of negative influence of the child's character (Y) by 0.824.